The relationship between constitutional equality and substantive review - CHNG, Wei Yao, Kenny (Institutional Knowledge at Singapore Management University, 2023)
General equality rights in written constitutions – rights stating the ideal of equality without specifying categories of impermissible differentiation – have often been effected through the idea of equality as rationality. Equality as rationality demands that differentiations between like entities have to be rationally justifiable. Such equality rights are applicable to legislation and executive action. This presents a prima facie overlap with substantive review in common law administrative law, since substantive review is also concerned about the rational justifiability of executive action. This raises three questions: (1) Are both sets of legal principles indeed similar? (2) Have courts managed to distinguish them in practice? (3) If not, then given that both sets of legal principles exist at different levels in the legal order, how can their similarity be rationalised? This article will study these questions, drawing upon Hong Kong and Singapore law as test cases.